1960
DOI: 10.1029/jz065i004p01273
|View full text |Cite
|
Sign up to set email alerts
|

Application of the multiple regression approach in evaluating parameters affecting water yields of river basins

Abstract: One of the principal problems in hydrology regression problems in hydrology will show is to define the effects of changes in land use that they do not conform to a multivariate on the regi'men of streams. Because of the normal distribution. Such variables as water many factors affecting streamflow, the in-year, degree of urbanization, percentage of ability even to recognize some of them, and basin in row crops, and miles of terracing are the lack of precision in describing them quanti-not randomly distributed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Not only is it possible to obtain almost equally good prediction equations on the basis of sets of different parameters, but judg ment must be exercised to avoid using phys ically irrelevant parameters or parameters which possess strong interdependence. Unfortunately wholly reliable, nonsubjective procedures to eliminate these personal factors do not exist at the present time [Sharp et al, 1960].…”
Section: Methods Of System Investigationmentioning
confidence: 96%
“…Not only is it possible to obtain almost equally good prediction equations on the basis of sets of different parameters, but judg ment must be exercised to avoid using phys ically irrelevant parameters or parameters which possess strong interdependence. Unfortunately wholly reliable, nonsubjective procedures to eliminate these personal factors do not exist at the present time [Sharp et al, 1960].…”
Section: Methods Of System Investigationmentioning
confidence: 96%
“…continued for a statistical model more applicable than the multiple regression approach for evaluating the many parameters affecting the water yielded as stream flow by river basins. The application of the multiple regression method to this problem was explored by Sharp, Gibbs, Owen, and Harris [1960], who concluded that assumptions inherent in the method are violated by hydrologic data, that common tests of significance generally applied to the results derived from such methods are questionable, and that confidence may be falsely placed in estimates obtained from estimating equations resulting from regression analyses. It was further indicated that the applicability of some of the more modern statistical techniques to the problems confronting the project should be investigated.…”
Section: Department Of Interior the Search Has Beenmentioning
confidence: 99%
“…Matalas and Reiher [1967] concluded that factor analysis is still largely undeveloped technically, and there are serious doubts as to its usefulness. However, the limitations of the normal multiple regression approach to water yield studies were pointed out in detail by Sharp et al [1960]. Snyder [1962] concluded that, for hydrologic studies, multivariate analysis offers the more satisfactory solution to the problem of estimating independent effects when the independent variables are correlated.…”
Section: Introductionmentioning
confidence: 99%